2002
DOI: 10.1046/j.1469-8137.2000.00536.x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis‐like cell death of Brassica napus leaf protoplasts

Abstract: Summary• The cleavage of nuclear DNA into oligonucleosomal fragments that is the hallmark of apoptosis in animal cells occurs during the culture of Brassica napus leaf protoplasts.• The changes in nuclei of cultured Brassica napus leaf protoplasts were studied by propidium iodide (PI) and 4 ′ , 6-diamino-2-phenylindole, dihydrochloride (DAPI) staining, transmission electron microscopy, flow cytometry analysis, and DNA laddering staining with ethidium bromide and Southern hybridization.• Free 3 ′ -OH termini of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 34 publications
(39 reference statements)
2
16
0
Order By: Relevance
“…Before plant regeneration can occur, protoplasts must undergo a process of dedifferentiation. Previously, we showed that Brassica napus leaf protoplasts initiate senescence during the isolation process and die via a process of apoptosis, similar to that observed in animal cells but with several morphological differences (Watanabe et al 1998;Watanabe et al 2002).…”
supporting
confidence: 56%
“…Before plant regeneration can occur, protoplasts must undergo a process of dedifferentiation. Previously, we showed that Brassica napus leaf protoplasts initiate senescence during the isolation process and die via a process of apoptosis, similar to that observed in animal cells but with several morphological differences (Watanabe et al 1998;Watanabe et al 2002).…”
supporting
confidence: 56%
“…Protoplasts were isolated from young expanded leaves of different iron treatments as described previously (Watanabe et al, 2002). The protoplasts were washed and re-suspended in 0.6 M sorbitol in 5 mM MES buffer (pH 5.8) and 5 mM CaCl 2 , and loaded with 100 μM H 2 DCF-DA for 30 min in darkness.…”
Section: Methodsmentioning
confidence: 99%
“…Protoplasts were isolated and fixed in 2% glutaraldehyde in sorbitol buffer (10 mM phosphate buffer, 0.6 M sorbitol, pH 7.4) for 2 h at room temperature and stained with DAPI (Watanabe et al, 2002). The protoplasts were washed and re-suspended in the sorbitol buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Strong blue DAPI stain characterized healthy cyanobacterial cells; however, cells with features of apoptosis exhibited weaker DAPI stain (Zheng et al, 2013). Likewise, DAPI-stained Brassica napus leaf protoplasts under fluorescence microscopy clearly showed enlarged nuclei with condensed chromatin (Watanabe et al, 2002).…”
Section: Discussionmentioning
confidence: 97%